Penerapan Konsep Divergence pada Indikator Momentum MACD - T. Syifa Fadrizha Nanda (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
Technical analysis was designed to provide historical information on price movements and serves as a tool for both investors and traders to capture ​​price movements in a market in order to forecast the possibilities of what might happen in the future. This study aims to test the performance of the momentum indicator (MACD) on identifying changes in market trends, by applying the concept of divergence between price movements and momentum indicator developments. This study is an applied research on the concept of divergence using a quantitative approach. Cross-sectional data from market movements (IDX) and indicators movements on the MACD oscillator during 2014-2021 (8 years) on daily time frame were used in this study. Observations on indicator movements and price movements are performed to detect divergence generated by MACD line and histogram using 26, 12, and 9 MACD parameters. Tradingview charting platform was used as a tools to analysis. This study prove that the divergence signal on MACD oscillators can be relied on to detect changes in the strength of the price movement trends. Furthermore, this study concludes that this signal can be used as an early warning signal to anticipate changes in trends. Keywords: Divergence; Momentum Indicator; MACD; Technical Analysis.